If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 3) + -4 = 2x + 5 Reorder the terms: 2(3 + 2x) + -4 = 2x + 5 (3 * 2 + 2x * 2) + -4 = 2x + 5 (6 + 4x) + -4 = 2x + 5 Reorder the terms: 6 + -4 + 4x = 2x + 5 Combine like terms: 6 + -4 = 2 2 + 4x = 2x + 5 Reorder the terms: 2 + 4x = 5 + 2x Solving 2 + 4x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 4x + -2x = 5 + 2x + -2x Combine like terms: 4x + -2x = 2x 2 + 2x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 2x = 5 + 0 2 + 2x = 5 Add '-2' to each side of the equation. 2 + -2 + 2x = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 5 + -2 2x = 5 + -2 Combine like terms: 5 + -2 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| -2(r+7)=14 | | 2x^2+12x+30= | | 4+4s=-8 | | -12/s=4 | | 2+(15)x=-7 | | 7-5x=10-(6x-7) | | 4x(x-12)=20 | | 2+3b=c | | 7r-15=3r+21 | | -6(8f+3)=26-7f | | m3-7=-10 | | 6-2(x-3)+4=4(2-3x) | | 12=-2-4 | | 7y+6x=6 | | -9a+45=-18 | | 3xsquared-24x+45=0 | | 16=-8c+9c | | (9x+2)(9x-1)=9x^2+3x-2 | | Y=0(-3)+-4 | | 5(5x-6)=67.5 | | 3x^2+15x+30= | | 8(n+1)-1=3(8+3n)-3 | | -x-13=-31 | | -6=3u4+12 | | y=4(-3)+3 | | 3x^2+15x+25= | | -6x^2-20x+16=0 | | (9x+2)(9x-1)=x | | 3x-17=x-1 | | 16x^4-64=0 | | 2x+11=43-3x | | 15-2(4)= |